Testing Perspectives of Fog‐Based IoT Applications - Chawla, Priyanka; Chawla, Rohit (Fog and Edge Computing, 2019)
Fog computing paradigm is a viable option for the development of Internet‐of‐Things (IoT) applications. This chapter starts with an explanation of the fundamental concepts of fog computing paradigm and associated benefits if adopted for the implementation of IoT applications. It deliberates testing perspectives of the smart applications in the area of home, health, and transport. Testing approaches and solutions are illustrated and compared based on their outcomes. The chapter proposes evaluation criteria relevant to the three smart technologies viz. smart home, smart health, and smart transport to assess the existing work. The chapter concludes with a discussion on open issues and future research directions from the perspectives of testing and future enhancements for the smart technologies. Certain evaluation criteria have also been presented for the assessment of existing work and to ascertain limitations and research directions.